MEMAHAMI KOMUNIKASI LINGKUNGAN DAN FRAMING SEBAGAI PRAKSIS PERUBAHAN SOSIAL - Achmad Hamudi Assegaf; Faizin Faizin; Tjondroargo Tandio (Universitas Prof. Dr. Moestopo (Beragama), 2022)
Human civilization, especially with its exploitative and unsustainable development activities of the last two centuries, has made environmental issues and climate change an unavoidable discussion for the public. Various ecological issues and crises are increasingly threatening the world, including Indonesia. Along with the development of information technology, the internet, and digital media, discourses related to environmental issues are becoming increasingly prominent. However, environmental communication, especially framing, is often misunderstood as a mere transmission of information, persuasion, or manipulation. The term 'slacktivism' also emerged to address the new trend of lazy activism that relies only on clicks and social media performances. This article is a literature study with a descriptive qualitative method that aims to comprehend how environmental communication and framing can be applied as praxis to address political-ecological issues. Researchers found that strategic and effective environmental communication is an integral process that is not only able to increase public awareness and understanding but also moves the community to engage more and actively participate in bringing about change. The use of social media also plays a role in gaining attention, support, and a large-scale and massive network of social-environmental activism.